2018
DOI: 10.1002/jcp.27441
|View full text |Cite
|
Sign up to set email alerts
|

Between an ugly truth and a perfect lie: Wiping off fearful memories using beta‐adrenergic receptors antagonists

Abstract: Psychiatric disorders such as anxiety, phobias, and post-traumatic stress disorder are considered of high global prevalence. Currently, a therapeutic approach to treat these disorders using beta-blockers, which antagonize the beta-adrenergic receptors (B1, B2, and B3) is being studied. This approach claims that beta-blockers, such as propranolol, inhibit fear memory reconsolidation. However, there are several studies refuting such claims by discrediting their experimental design and pointing out both the drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
(104 reference statements)
0
6
0
Order By: Relevance
“…In general, the studies in cultured cells indicate that β 1 -AR is more resistant to agonist-mediated downregulation than β 2 -AR [7][8][9]. Since β 2 -ARs are distributed extensively throughout the body, wherein they mediate the response to sympathetic discharges in many organs and tissues, including immune and central nervous systems [10][11][12], there is considerable interest in their regulation. At present, an in vitro analysis of the effects of β-blockers with different signaling profiles on β 2 -AR density is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the studies in cultured cells indicate that β 1 -AR is more resistant to agonist-mediated downregulation than β 2 -AR [7][8][9]. Since β 2 -ARs are distributed extensively throughout the body, wherein they mediate the response to sympathetic discharges in many organs and tissues, including immune and central nervous systems [10][11][12], there is considerable interest in their regulation. At present, an in vitro analysis of the effects of β-blockers with different signaling profiles on β 2 -AR density is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, the agents was not found to affect declarative memory impairment. [38] For a long time, there have been suspicions linking beta-blockers with the risk of developing depression, and lipophilic beta-blockers have been associated with an increased risk compared to non-lipophilic ones. [39] In a recent published study on the subject from 2002, which included 15 studies with a total group of over 35,000 patients, Ko and colleagues proved that there is no significant effect of using βblockers on the development of depression, and there is no relationship between the lipophilic profile and non-lipophilic agent and the risk of symptoms during therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The interview focused on depicting the most aversive aspects of the narrative. Reconsolidation is expected to initiate 3–10 mins following the memory reactivation and to last for about 2–6 h ( 21 ). It has been previously shown that the higher the trait anxiety of an individual, the less likely it is that propranolol reduces fear by disrupting memory consolidation, e.g., Soeter and Kindt ( 22 ).…”
Section: Methodsmentioning
confidence: 99%